Effect of Tapioca Binder Concentration on the Quality of Charcoal Briquettes Produced from Oil Palm Trunk and Laban Wood - Hisyammudin Hisyammudin; Zakwan Zakwan; Heri Purwanto (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
This study examined the effect of tapioca binder concentration on the quality of charcoal briquettes produced from oil palm trunk and laban wood. A non-factorial Completely Randomized Design was applied using five binder concentrations: V1 (10%), V2 (15%), V3 (20%), V4 (22.5%), and V5 (25%), with three replications. Moisture content, ash content, and calorific value were evaluated. One-way analysis of variance showed a highly significant treatment effect for every parameter (p < 0.001), and Duncan’s Multiple Range Test at the 5% level separated all treatment means. Increasing binder concentration raised moisture content from 4.131% to 6.175% and ash content from 3.263% to 4.900%, while calorific value decreased from 7,185.33 to 6,325.98 cal/g. All treatments met SNI 01-6235-2000. The best treatment was V1, consisting of 47.5% oil palm trunk charcoal, 47.5% laban wood charcoal, and 10% tapioca binder. The results demonstrate that controlling binder concentration is essential for balancing particle cohesion and thermal quality.